360° virtual reality video for the acquisition of knot tying skills: A randomised controlled trial. (June 2018) - Yoganathan, S.; Finch, D.A.; Parkin, E.; Pollard, J.
Abstract: Background: 360° virtual reality (VR) video is an exciting and evolving field. Current technology promotes a totally immersive, 3-dimensional (3D), 360° experience anywhere in the world using simply a smart phone and virtual reality headset. The potential for its application in the field of surgical education is enormous. The aim of this study was to determine knot tying skills taught with a 360-degree VR video compared to conventional 2D video teaching. Material and methods: This trial was a prospective, randomised controlled study. 40 foundation year doctors (first year postgraduate) were randomised to either the 360-degree VR video (n = 20) or 2D video teaching (n = 20). Participants were given 15 min to watch their allocated video. Ability to tie a single handed reef knot was then assessed against a marking criteria developed for the Royal College of Surgeons, England, (RCSeng) Basic Surgical Skills (BSS) course, by a blinded assessor competent in knot tying. Each candidate then underwent further teaching using Peyton's four step model. Knot tying technique was then re-assessed. Results: Knot tying scores were significantly better in the VR video teaching arm when compared with conventional (median knot score 5.0 vs 4.0 p = 0.04). When used in combination with face to face skills teaching this difference persisted (median knot score 9.5 vs 9.0 p = 0.01). More people in the VR arm constructed a complete reef knot than in the 2D arm following face to face teaching (17/20 vs 12/20). No difference between the groups existed in the time taken to construct a reef knot following video and teaching (median time 31.0s vs 30.5s p = 0.89). Conclusion: This study shows there is significant merit in the application of 360-degree VR video technology in surgical training, both as an independent teaching aid and when used as an adjunct to traditional face to face teaching. Highlights: To determine knot tying skills taught with a 360-degree Virtual Reality video compared to 2- Dimensional video teaching. Using video teaching alone, knot tying scores were significantly better in the 360-degree Virtual Reality video arm. More people in the 360-degree Virtual Reality video arm constructed a complete reef knot than in the 2-Dimensional arm.